2018
DOI: 10.2217/nnm-2017-0345
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of miRNA-204-5p By PEGylated Polymer Nanoparticles for Colon Cancer Therapy

Abstract: Our study demonstrates a convenient miRNA delivery system that targets tumor tissue and exerts tumor suppressive function, thus demonstrating a potential new therapeutic option for colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Our and other studies have demonstrated that miR-204-5p could increase the sensitivity of tumor cells to chemotherapeutic drugs. 8,9,23,24 In this study, our in vitro assays confirmed that exosomal miR-204-5p could efficiently enhance the cytotoxicity of 5-FU by increasing 5-FU-induced apoptosis. Liu et al showed that engineered tumor-targeting hEVs are promising natural vectors to overcome MDR.…”
Section: F I G U R Esupporting
confidence: 70%
“…Our and other studies have demonstrated that miR-204-5p could increase the sensitivity of tumor cells to chemotherapeutic drugs. 8,9,23,24 In this study, our in vitro assays confirmed that exosomal miR-204-5p could efficiently enhance the cytotoxicity of 5-FU by increasing 5-FU-induced apoptosis. Liu et al showed that engineered tumor-targeting hEVs are promising natural vectors to overcome MDR.…”
Section: F I G U R Esupporting
confidence: 70%
“…A recent work evaluated an oral delivery system intended for treatment of colon cancer by encapsulating hSET1 antisense and SN38 anticancer in nanoparticles with results effective against HT29 cells. Also, more recently it was proposed against CRC to encapsulate miR-204-5p with poly ( d , l -lactide- co -glycolide)/poly ( l -lactide)-block-poly (ethylene glycol)-folate polymer to promote apoptosis and inhibit cell proliferation in an in vitro xenograft model with Luc-HT-29 [8587]. Although it is a very promising area in the treatment against cancer, it still requires further evaluation of the role of different vectors to find the most suitable and safe, efficient and without long-term toxicity for its application in humans.…”
Section: Therapeutic Strategymentioning
confidence: 99%
“…In some cases, this leads to RNA loading within the PLGA NP core, while in others the RNA is bound to the exterior of the PLGA NP . In an alternative approach, copolymers of PEI‐PLGA, PLL‐PLGA, or PLA‐PLGA can be used to synthesize miRNA‐loaded NPs. With these various formulations, encapsulation efficiencies ranging from 78.3% up to 95.1% have been reported.…”
Section: Polymer Nanocarriers For Mirna Deliverymentioning
confidence: 99%
“…Excitingly, several other PLGA NP miRNA nanocarriers have achieved in vivo success. For example, PLGA NPs have been used to treat multiple myeloma via miR‐34a delivery, hepatic carcinoma via miR‐99a delivery, and colon cancer via miR‐204 delivery in murine models. These studies demonstrate the substantial potential of PLGA NPs as miRNA delivery vehicles.…”
Section: Polymer Nanocarriers For Mirna Deliverymentioning
confidence: 99%